Investigation of Blastocystis hominis Frequency in Patients with Diabetes by Microscopy and Conventional PCR Methods - Maksut Şahin; Zeynep Taş Cengiz; Ahmed Galip Halidi; Selahattin Aydemir (Iranian Journal of Parasitology, 2023)
Background: We aimed to determine the frequency and subtype of B. hominis in diabetic patients.